2013
DOI: 10.1111/bjh.12435
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the molecular pathogenesis of myelodysplastic syndromes

Abstract: SummaryThe advent of novel genomic sequencing technologies has aided the identification of somatically acquired genetic abnormalities up to 80% of myelodysplastic syndrome (MDS) patients. Novel recurrent genetic mutations in pathways such as RNA splicing, DNA methylation and histone modification and cohesion complexes, underscore the molecular heterogeneity seen in this clinically varied disease. Functional studies to establish a causative link between genomic aberrations and MDS biogenesis are still in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 155 publications
0
37
0
1
Order By: Relevance
“…13 Unlike myeloproliferative neoplasms, in which a mutation in 1 of just 3 genes (JAK2, CALR, and MPL) that constitutively activate hematopoietic growth factor receptor signaling is present in .85% of cases, no single mutation class is dominant in MDS. Mutations in SF3B1 and TET2, each mutated in 20% to 25% of patients with MDS, are the most commonly described abnormalities to date.…”
Section: Introductionmentioning
confidence: 99%
“…13 Unlike myeloproliferative neoplasms, in which a mutation in 1 of just 3 genes (JAK2, CALR, and MPL) that constitutively activate hematopoietic growth factor receptor signaling is present in .85% of cases, no single mutation class is dominant in MDS. Mutations in SF3B1 and TET2, each mutated in 20% to 25% of patients with MDS, are the most commonly described abnormalities to date.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis of MDS has been recently elucidated by novel DNA sequencing technologies, and up to 80% of patients are known to have somatic genetic mutations [9][10][11]. Among the many genetic mutations, several genes such as TP53, RUNX1, ETV6, EZH2, ASXL1, U2AF1, and SRSF2 have been identified to have poor prognostic significance in MDS [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…ultiple classes of genetic aberrations have been suggested as the cause of myelodysplastic syndromes (MDS) (1,2), including mutations in signal transduction, transcription factors, and epigenetic modifiers (3)(4)(5). Interestingly, recent genomewide sequencing studies revealed that mutations in genes encoding splicing factors are commonly associated with MDS and other hematological malignancies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%